The third international standard for anti‐D immunoglobulin: international collaborative study to evaluate candidate preparations. Issue 7 (19th July 2019) - Fox, Bernard; Sharp, Giles; Atkinson, Eleanor; Roberts, Graham; Rigsby, Peter; Studholme, Lucy
Abstract : Background and Objectives: The purpose of the study was to evaluate a lyophilized anti‐D immunoglobulin preparation to serve as a replacement WHO International Standard for the calibration of potency assays of anti‐D immunoglobulin products. Such products are used to prevent haemolytic disease of the foetus and newborn due to maternal alloanti‐D. Materials and Methods: The candidate 3rd International Standard for anti‐D immunoglobulin (16/332) was evaluated and calibrated against the 2nd International Standard for anti‐D immunoglobulin (01/572), along with a coded duplicate, a second candidate preparation (16/278) and a comparability sample (16/272) in an international collaborative study. Twenty of 21 laboratories in 15 countries performed one or more of the three European Pharmacopoeia reference methods. Results: The overall geometric mean potency (from all methods) of the candidate 3rd International Standard, 16/332, was 296·6 IU/ampoule, with inter‐laboratory variability, expressed as % GCV, of 4·7%. SE‐HPLC of the immunoglobulin preparations demonstrated combined monomeric and dimeric IgG peak areas of >95% for all samples. Accelerated stability studies have shown both 16/332 and 16/278 to be very stable for long‐term storage at −20°C. Conclusions: Preparation 16/332 was established by the World Health Organisation Expert Committee on Biological Standardization as the 3rd International Standard for anti‐D immunoglobulin with an assigned potency of 297 IU/ampoule.